Effectiveness of a machine learning classifier model (Journal of Advances and Scholarly Researches in Allied Education, 2025)
As a statistical tool, predictive modelling may foretell how something will act in the future. In order to foretell how people will act in the future, machine learning has become a popular tool. Determining which of the many accessible algorithms is best suited to the data at hand is an intriguing challenge. The field of study that finds the greatest value in predictive modelling is educational data mining. Accurately predicting undergraduate students' grades has several benefits for both students and teachers. Students might be more motivated to choose their future endeavours with the support of early prediction. Using data gathered from undergraduate studies, this study displays the outcomes of many machine learning methods. It uses data obtained from undergraduate studies to assess the efficacy of several machine learning methods. Choosing the proper characteristics and the right prediction algorithm are two big problems that are addressed.